2020
DOI: 10.1101/2020.09.14.297143
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Contextual effects in sensorimotor adaptation adhere to associative learning rules

Abstract: Two influential paradigms, sensorimotor adaptation and eyeblink conditioning, have deepened our understanding of the theoretical and neural foundations of motor learning, and in particular, the role of the cerebellum. Although there has been some cross-pollination between these two lines of research, they typically operate within distinct theoretical frameworks, with the incremental updating of an internal forward model explaining adaptation, and associative learning processes explaining eyeblink conditioning.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 143 publications
(417 reference statements)
1
4
0
Order By: Relevance
“…In the latter, the motor commands and visual feedback serve as equivalents for the CS and US, respectively. Consistent with this notion, we have recently shown that when temporal constraints are imposed, two signature phenomena of classical conditioning, differential conditioning and compound conditioning, are observed in visuomotor adaptation 39 .…”
Section: Discussionsupporting
confidence: 61%
“…In the latter, the motor commands and visual feedback serve as equivalents for the CS and US, respectively. Consistent with this notion, we have recently shown that when temporal constraints are imposed, two signature phenomena of classical conditioning, differential conditioning and compound conditioning, are observed in visuomotor adaptation 39 .…”
Section: Discussionsupporting
confidence: 61%
“…This could explain why strong reinforcement-specific adjustments were maintained on Day 2 in the reward group, even though no rewards were at stake anymore. Such associative learning processes are known to strongly influence autonomic responses (Pool et al, 2019), inhibitory control (Avraham et al, 2020;Lindströ m et al, 2019;Verbruggen et al, 2014), decision making (Lindströ m et al, 2019), and even sensorimotor adaptation (Avraham et al, 2020) in humans. We propose that associative learning may also contribute to the durable influence of motivation on motor skill learning (Abe et al, 2011;Sporn et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This could explain why strong reinforcement-specific adjustments were maintained on day 2 in the reward group, even though no rewards were at stake anymore. Such associative learning processes are known to strongly influence autonomic responses (Pool et al, 2019), inhibitory control (Avraham et al, 2020b; Lindström et al, 2019; Verbruggen et al, 2014), decision making (Lindstrom et al, 2019) and even sensorimotor adaptation (Avraham et al, 2020) in humans. We propose that associative learning may also contribute to the durable influence of motivation on motor skill learning (Abe et al, 2011; Sporn et al, 2020).…”
Section: Discussionmentioning
confidence: 99%